2013
DOI: 10.1101/gad.211243.112
|View full text |Cite
|
Sign up to set email alerts
|

The DEAH-box helicase DHX36 mediates dendritic localization of the neuronal precursor-microRNA-134

Abstract: Specific microRNAs (miRNAs), including miR-134, localize to neuronal dendrites, where they control synaptic protein synthesis and plasticity. However, the mechanism of miRNA transport is unknown. We found that the neuronal precursor-miRNA-134 (pre-miR-134) accumulates in dendrites of hippocampal neurons and at synapses in vivo. Dendritic localization of pre-miR-134 is mediated by the DEAH-box helicase DHX36, which directly associates with the pre-miR-134 terminal loop. DHX36 function is required for miR-134-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(135 citation statements)
references
References 32 publications
7
128
0
Order By: Relevance
“…RHAU has been shown to specifically bind several non-quadruplex RNAs (1,25); however, this is the first time it has been shown to have affinity for adenosine-rich single-stranded RNA. Whether this affinity is specific to the adenosine-rich stretch of BC200 or RHAU binds a broad spectrum of RNAs containing similar repetitive elements remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RHAU has been shown to specifically bind several non-quadruplex RNAs (1,25); however, this is the first time it has been shown to have affinity for adenosine-rich single-stranded RNA. Whether this affinity is specific to the adenosine-rich stretch of BC200 or RHAU binds a broad spectrum of RNAs containing similar repetitive elements remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…RHAU has also garnered attention for complicity with several non-coding RNAs, both in the regulation of subcellular localization of specific microRNAs and in the remodeling of quadruplexes within the 5Ј-region of the telomerase RNA (22)(23)(24)(25). Furthermore, RHAU has been related to critical roles in development, differentiation, and immunity (26 -29).…”
mentioning
confidence: 99%
“…The identity of this repressor molecule and whether it is subjected to activity regulation in neurons is, however, unknown [31]. Moreover, it was recently shown that the DEAH-box protein DHX36, which mediates the transport of pre-miR-134 to dendrites, protects the pre-miR-134 from Dicer processing by binding to the terminal loop structure [32] (figure 1c, right panel). As reported in §1, AGO proteins also participate in miRNA biogenesis, but evidence about this aspect of AGO function in neurons has still not been provided.…”
Section: Regulation Of Mirnas By Neuronal Activity (A) Activity-depenmentioning
confidence: 99%
“…A major advance in the field is a recent study that provided insight into the transport and sorting of pre-miR-134, the precursor form of miR-134, in dendrites of hippocampal neurons (Bicker et al, 2013).…”
Section: The Mainstream: Mirnasmentioning
confidence: 99%